P-199 Planning for the future: growing our own Clinical Nurse Specialists. (19th November 2022) - Griffith, Sue; Stevens, Alison; Lew, Eva; Sweeting, Matt; Gray, Alison
Abstract : Background: A shortage of experienced nurses suitably qualified to work as Clinical Nurse Specialists (CNS) in palliative care, was recognised and predicted many years ago (Skills for Health, 2013). Shortages in our healthcare workforce are now so severe that they are defined as endemic (King's Fund, 2022). With no recognised qualification or set experience required to work as a CNS (National Council for Palliative Care, 2016), this presents the problem of how to develop willing nurses into this role. Aims: To create a robust training programme of sufficient education, experience and support to produce nurses who are competent to work at 'specialist level' (NHS England, 2016). Method: A hospice panel of senior practitioners, guided by a published concept analysis (Griffith, 2018. Int J Palliat Nurs. 24: 399), devised a training programme and set of competencies to support the progression of registered nurses to CNS level. The two-year training programme includes working within care teams alongside CNS mentors, as well as placements in the in-patient unit and with outside agencies, such as hospital palliative care, heart failure, COPD and oncology teams. The trainee CNSs also receive clinical supervision and attend monthly teaching sessions covering topics designed to support the necessary learning, including advanced symptom control and communication skills. Promotion to full CNS will be on completion of a set of competencies, and approval of the panel. Results: It is too early to report results at this stage. However, five trainee CNSs were employed in the last seven months, and are already making progress with learning and competency completion. Conclusion/Learning: At a time when nationally there are minimal applicants for full CNS positions, successful recruitment suggests that this project offers an opportunity to address a gap in the workforce. The robustness of the competencies and training process also ensures that in future, this hospice can hope to have five fully competent CNSs to complement the existing team. Ongoing evaluation/refinement is part of the process.